Heavy metal deposition temperature tuned spin pumping efficiency control in permalloy/tantalum bilayers. (5th March 2023) - Priyanka, P; Makani, N H; Banerjee, R; Sarkar, I
Abstract: Spin pumping is a key property for spintronic application that can be realized in heavy metal/ferromagnet bilayers. Here we demonstrate the possibility of improving spin pumping in permalloy (Py)/tantalum (Ta) bilayers through control of Ta heavy metal deposition temperature. Through a combination of structural and ferromagnetic resonance based magnetization dynamics study, we reveal the role of Ta deposition temperature in improving spin mixing conductance which is a key parameter for spin pumping across the Py/Ta interface. The results show that by depositing Ta above room temperature, a high spin mixing conductance of 7.7 ×10 18 m −2 is obtained with α -Ta layer. The results present an understanding of the correlation between heavy metal deposition temperature and interface structure improvement and consequent control of spin pumping in Py/Ta bilayers.